Piperine-Chlorogenic Acid Hybrid Inhibits the Proliferation of the SK-MEL-147 Melanoma Cells by Modulating Mitotic Kinases - Carolina Girotto Pressete; Flávia Pereira Dias Viegas; Thâmara Gaspar Campos; Ester Siqueira Caixeta; João Adolfo Costa Hanemann; Guilherme Álvaro Ferreira-Silva; Bruno Zavan; Alexandre Ferro Aissa; Marta Miyazawa; Claudio Viegas; Marisa Ionta (MDPI AG, 2023)
Melanoma is considered the most aggressive form of skin cancer, showing high metastatic potential and persistent high mortality rates despite the introduction of immunotherapy and targeted therapies. Thus, it is important to identify new drug candidates for melanoma. The design of hybrid molecules, with different pharmacophore fragments combined in the same scaffold, is an interesting strategy for obtaining new multi-target and more effective anticancer drugs. We designed nine hybrid compounds bearing piperine and chlorogenic acid pharmacophoric groups and evaluated their antitumoral potential on melanoma cells with distinct mutational profiles SK-MEL-147, CHL-1 and WM1366. We identified the compound named PQM-277 (3a) to be the most cytotoxic one, inhibiting mitosis progression and promoting an accumulation of cells in pro-metaphase and metaphase by altering the expression of genes that govern G2/M transition and mitosis onset. Compound 3a downregulated FOXM1, CCNB1, CDK1, AURKA, AURKB, and PLK1, and upregulated CDKN1A. Molecular docking showed that 3a could interact with the CUL1-RBX1 complex, which activity is necessary to trigger molecular events essential for FOXM1 transactivation and, in turn, G2/M gene expression. In addition, compound 3a effectively induced apoptosis by increasing BAX/BCL2 ratio. Our findings demonstrate that 3a is an important antitumor candidate prototype and support further investigations to evaluate its potential for melanoma treatment, especially for refractory cases to BRAF/MEK inhibitors.